Exploring the Impact of Exchange: A Study of Central Asian Experiences with U.S.-Sponsored Academic Exchange Programs - Cole, Marilyn (My University, 2018)
This thesis examines the trends and impact of U.S.-sponsored academic exchange programs available for Central Asian citizens. I analyze how these exchange programs have fared since their establishment to the present day by outlining the scale of these programs, exploring how participants have been affected by their exchange experience, and conclude by providing recommendations for possible directions exchanges can take in the future. Within this research project, I examine prevalent trends of Central Asian citizens participating in U.S.-sponsored exchange programs. Through in-person interviews and participants' online statements, I identify broader issues that are important in the exchange experience. This thesis aims to assist local citizens of the United States and Central Asia in understanding why Central Asian citizens should continue to pursue academic exchanges and why policy makers should prioritize these exchange programs for strategic diplomacy planning.
Thesis (Master's)--University of Washington, 2018
Keywords: Central Asia; exchange programs; FLEX; Fulbright; SUSI; U.S.-sponsored exchanges; Educational administration; East European studies; Russian history; To Be Assigned